BRAND COMMUNICATION STRATEGY TO GENERATE BRAND EXPERIENCE (CASE STUDY : KIKONOXA) - NAZARETH HUTAPEA - 29116057, YITZHAK
Fashion brand must be associated with the user lifestyle in specific culture especially outdoor brand. Kikonoxa is modern urban outdoor brand that offer the durability and the stylish lifestyle for the customer. From the brand founded there are several misconception and gap about the perceived value of the brand and the connection between user of the brand and the brand itself, the connection seems to be missing link. The lack of engagement from the customer and the brand drive the brand into weak connection and association experience. In modern fashion brand era, brand been charged to offer more than a product and service moreover experience. The purpose of this research is to know the extent which the customer of a brand feels the experience offered by a brand by examining the gap between the identity of brand and users that have been delivered with various ways and strategies also examine competition with competitors in existing markets. This research done using qualitative methods. The analysis using brand identity analysis with AC2ID methodology and marketing mix analysis states that brand needs to generate the customer experience by improve some operational lines as the cause of the missinglink in betweenand analysis using Customer-Based Brand Equity analysis contain of questionnaires and observations for competitor analysis thatproduces an outcome stating that as a brand Kikonoxa has a gap between brand and customer in terms of identity and in delivering brand value strategies that drive the brand into slow growth. All of the result analyzed using fishbone analysis that connected to the CBBE model approach questionnaire and competitor analysis to explore the cause for the brand weak brand experience to define the root cause of the brand experience problem. From this research all of the problem narrowed into operational based problem consist of brand development and brand optimization with create a looping phase development program contain of strength in philosophy by building the brand identity, product realization by choosing the right vendor, error minimization by building a team and engagement by connecting brand value integrated with social media communication strategy consist of ads optimization, hashtag engagement, brand promotion and collaboration with external environment that covered by brand information system as the base of improvement andbrand must create one-year general guidelines that connect the brand and market with creating the monthly schedule that contain the brand needs and the actual resources in order to keep the brand deliver the experience through effective and efficient workflow.